A nano nickel-based molecular sieve composite material with core-shell structure and its preparation method and application

By preparing a core-shell structured nano-nickel-based molecular sieve composite material, the steric hindrance problem of existing catalysts in catalyzing macromolecular sulfides was solved, achieving a highly efficient hydrodesulfurization effect, especially showing excellent performance in the conversion and desulfurization rate of 4,6-dimethyldibenzothiophene.

CN115999635BActive Publication Date: 2025-01-07FUDAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211656522.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2025-01-07
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

Existing hydrodesulfurization catalysts suffer from significant steric hindrance when catalytically converting large organic sulfur molecules, resulting in low hydrodesulfurization efficiency.

Method used

A nano-nickel-based molecular sieve composite material with a core-shell structure is used. The core phase is USY zeolite, and the shell phase is Al-MFI molecular sieve rudimentary crystals loaded with nickel nanoparticles. It is prepared by layer-by-layer assembly and impregnation method. Nickel nanoparticles are uniformly coated on the outer surface of USY molecular sieve to form a thin shell layer.

Benefits of technology

It improves the diffusion ability of macromolecular sulfides, enhances the dispersibility of nickel nanoparticles, reduces mass transfer resistance, and improves the hydrodesulfurization reaction activity, achieving highly efficient hydrodesulfurization performance. The conversion rate and desulfurization rate of 4,6-dimethyldibenzothiophene reach 99.2% and 99.1%, respectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115999635B_ABST
    Figure CN115999635B_ABST
Patent Text Reader

Abstract

The present invention relates to a hydrodesulfurization catalyst, and in particular to a nano nickel-based molecular sieve composite material with a core-shell structure, a preparation method and an application thereof, wherein the composite material is a core-shell structure, the core phase is USY zeolite, the shell phase is Al-MFI molecular sieve crystals loaded with nickel nanoparticles, and the USY zeolite is 50-80% by weight, and the Al-MFI molecular sieve crystals loaded with nickel nanoparticles are 20-50% by weight. Compared with the prior art, the present invention solves the problem that the hydrodesulfurization catalyst in the prior art has significant steric hindrance and low hydrodesulfurization efficiency when catalytically converting organic sulfur molecules with larger sizes, and the composite material is applied to hydrodesulfurization to achieve the advantages of high catalytic activity and large processing capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hydrodesulfurization catalyst, in particular to a nano nickel-based molecular sieve composite material with a core-shell structure and a preparation method and application thereof. Background Art

[0002] At present and for a long time to come, traditional fossil fuels will still be the dominant energy source for social and economic development. However, the combustion and use of fossil fuels release a large amount of pollutants such as sulfur oxides and nitrogen oxides, which seriously harm the ecological environment and human health. With the increasing awareness of green economy and sustainable development, more stringent environmental protection regulations and fuel vehicle emission standards have been introduced to cope with increasingly severe environmental problems.

[0003] Sulfur in automotive fuel oil mainly exists in the form of thiophene compounds such as benzothiophene, dibenzothiophene and its substitutions, naphthiophene, etc. Most of them can be converted into straight-chain or branched hydrocarbons and hydrogen sulfide through traditional hydrodesulfurization technology, but the performance of deep hydrodesulfurization needs to be further improved. At present, the hydrodesulfurization catalysts widely used in industry are mainly bifunctional catalysts composed of bimetallic sulfides such as NiMoS / Al2O3 and CoMoS / Al2O3 and acid sites carried by Al2O3. Since the acid sites of Al2O3 are mainly located in narrow and uneven micropores, there is a significant steric hindrance when catalytically converting larger organic sulfur molecules such as dibenzothiophene and 4,6-dimethyldibenzothiophene, which reduces the efficiency of hydrodesulfurization.

[0004] Chinese patent CN202111589488.2 discloses a nano nickel-based MFI crystallite molecular sieve and its preparation method and application, including nano Al-MFI molecular sieve crystallite and nickel loaded on the nano Al-MFI molecular sieve crystallite. Its Al-MFI molecular sieve crystallite is to supplement the aluminum source after the pure silicon MFI crystallite is formed, perform secondary crystallization, and finally form Al-MFI molecular sieve crystallite, and the preparation process is relatively complicated. More importantly, the nano Al-MFI molecular sieve crystallite loaded with nickel in the patent has a low processing capacity in the hydrodesulfurization reaction. After research, the inventor found that this is mainly due to the large spatial resistance formed by the self-aggregation of the Al-MFI molecular sieve crystallite.

[0005] Therefore, the development of efficient deep hydrodesulfurization catalysts has important practical value for improving the clean use of fossil fuel oil. Summary of the invention

[0006] The purpose of the present invention is to solve at least one of the above problems and to provide a nano nickel-based molecular sieve composite material with a core-shell structure and its preparation method and application, so as to solve the problem that the hydrodesulfurization catalyst in the prior art has significant steric hindrance and low hydrodesulfurization efficiency when catalyzing the conversion of larger organic sulfur molecules. The composite material is applied in hydrodesulfurization to achieve the advantages of high catalytic activity and large processing capacity.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] The first aspect of the present invention discloses a nano nickel-based molecular sieve composite material with a core-shell structure. The composite material is a core-shell structure, the core phase is USY zeolite, and the shell phase is Al-MFI molecular sieve crystals loaded with nickel nanoparticles. In terms of weight percentage, USY zeolite is 50-80%, and Al-MFI molecular sieve crystals loaded with nickel nanoparticles are 20-50%.

[0009] Preferably, the thickness of the shell layer is 20-80 nm, the loading amount of nickel nanoparticles is 0.5-5 wt% of the total mass of USY zeolite and Al-MFI molecular sieve crystals, and the silicon-aluminum atomic ratio of the Al-MFI molecular sieve crystals is 35-200:1.

[0010] The second aspect of the present invention discloses a method for preparing the above-mentioned nano nickel-based molecular sieve composite material with a core-shell structure, comprising the following steps:

[0011] S1: dissolving the silicon source and the aluminum source in an aqueous solution of tetrapropylammonium hydroxide in sequence, and obtaining an Al-MFI molecular sieve crystal solution containing acidic sites after hydrothermal treatment;

[0012] S2: adding USY zeolite to a cationic polyelectrolyte solution and mixing it evenly, so that polycations are attached to the surface of the USY zeolite, and the free polycations are removed by centrifugal washing; then placing it in an anionic polyelectrolyte solution and mixing it evenly, so that polyanions are attached to the surface of the USY zeolite, and the free polyanions are removed by centrifugal washing; placing it in a cationic polyelectrolyte solution again and mixing it evenly, so that polycations are attached to the surface of the USY zeolite, and the free polycations are removed by centrifugal washing; repeating the above steps several times to increase the uniformity of the coating of the crystal particles, and obtaining a positively charged USY zeolite with attached polyelectrolyte;

[0013] S3: adding the positively charged USY zeolite with attached polyelectrolyte obtained in step S2 to the Al-MFI molecular sieve crystallite solution containing acidic sites obtained in step S1 and mixing them evenly, and under the action of charge matching, the Al-MFI molecular sieve crystallite is coated on the outer surface of the USY zeolite particles to obtain USY zeolite coated with the Al-MFI molecular sieve crystallite;

[0014] S4: centrifuging and washing the USY zeolite coated with Al-MFI molecular sieve crystals obtained in step S3, then placing it in a cationic polyelectrolyte solution and mixing it evenly, repeating step S2 to obtain the USY zeolite coated with Al-MFI molecular sieve crystals with a positive outer surface;

[0015] S5: adding the USY zeolite coated with Al-MFI molecular sieve crystals having positive outer surface obtained in step S4 to the Al-MFI molecular sieve crystal solution containing acidic sites obtained in step S1 again, performing secondary coating to adjust the thickness and uniformity of the shell layer, and repeating step S4 and the above steps several times to obtain a composite material;

[0016] S6: adding the composite material obtained in step S5 into an aqueous solution containing nickel ions to impregnate and load the nickel ions, and after washing, drying, calcining and reducing, obtaining the nano nickel-based molecular sieve composite material with a core-shell structure.

[0017] Preferably, in step S1,

[0018] The silicon source comprises one or more of tetraethyl orthosilicate, water glass and silica sol, the aluminum source comprises one or more of aluminum isopropoxide, aluminum nitrate nonahydrate, aluminum chloride hexahydrate and aluminum sulfate 18hydrate, and the molar ratio of silicon element in the silicon source, aluminum element in the aluminum source, tetrapropylammonium hydroxide and water is 1: 0.025-0.005: 0.15-0.6: 4.5-40;

[0019] The hydrothermal treatment includes two stages of hydrothermal crystallization reactions, which are low-temperature hydrothermal crystallization reaction and high-temperature hydrothermal crystallization reaction. The temperature of the low-temperature hydrothermal crystallization reaction is 50-110°C and the time is 50-160 minutes. The temperature of the high-temperature hydrothermal crystallization reaction is 120-170°C and the time is 30-100 minutes.

[0020] The size of the crystallite particles in the Al-MFI molecular sieve crystallite solution containing acidic sites is 6-20 nm.

[0021] Preferably, in step S2,

[0022] The size of the USY zeolite is 100-1000 nm, the cationic polyelectrolyte includes one or more of polydiallyldimethylammonium chloride, polyvinylpyridine and polyvinylamine, and the anionic polyelectrolyte includes but is not limited to one or more of sodium polystyrene sulfonate and sodium polyacrylate; the cationic polyelectrolyte solution is an aqueous solution of a cationic polyelectrolyte with a mass concentration of 0.1-10 wt%, and the anionic polyelectrolyte solution is an aqueous solution of an anionic polyelectrolyte with a mass concentration of 0.1-10 wt%;

[0023] The liquid-to-solid mass ratio when added to the cationic polyelectrolyte solution or the anionic polyelectrolyte solution is 10-50, the mixing time is 0.5-5h, and the steps are repeated 1-5 times.

[0024] Preferably, in step S3,

[0025] The liquid-to-solid mass ratio of the positively charged USY zeolite with attached polyelectrolyte to the Al-MFI molecular sieve crystal solution containing acidic sites is 10-50, and the mixing time is 1-24 hours.

[0026] Preferably, in step S4,

[0027] The cationic polyelectrolyte includes one or more of polydiallyldimethylammonium chloride, polyvinylpyridine and polyvinylamine, and the anionic polyelectrolyte includes but is not limited to one or more of sodium polystyrene sulfonate and sodium polyacrylate; the cationic polyelectrolyte solution is an aqueous solution of a cationic polyelectrolyte with a mass concentration of 0.1 to 10 wt%, and the anionic polyelectrolyte solution is an aqueous solution of an anionic polyelectrolyte with a mass concentration of 0.1 to 10 wt%;

[0028] The liquid-to-solid mass ratio when added to the cationic polyelectrolyte solution or the anionic polyelectrolyte solution is 10-50, the mixing time is 0.5-5h, and the steps are repeated 1-5 times.

[0029] Preferably, in step S5,

[0030] The liquid-to-solid mass ratio of USY zeolite coated with Al-MFI molecular sieve crystals with positive external surface to Al-MFI molecular sieve crystal solution containing acidic sites is 10-50, the mixing time is 1-24 hours, and the steps are repeated 1-5 times.

[0031] Preferably, in step S6,

[0032] The nickel ions in the aqueous solution containing nickel ions are derived from water-soluble nickel salts, including one or more of nickel nitrate, nickel chloride and nickel acetate;

[0033] The calcination atmosphere is air, the temperature is 200-800°C, and the time is 2-8h;

[0034] The reducing atmosphere is a hydrogen-protective gas atmosphere, the temperature is 200-800° C., and the time is 2-8 hours, wherein the volume fraction of hydrogen gas in the hydrogen-protective gas atmosphere is 5-15%.

[0035] The third aspect of the present invention discloses the use of the nano nickel-based molecular sieve composite material with a core-shell structure as described above as a catalyst in hydrodesulfurization.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The present invention adopts a layer-by-layer assembly method, uses a polycationic electrolyte to adjust the core phase surface to be positively charged, then coats the negatively charged MFI molecular sieve crystals on the outside of the core phase, and then uses an impregnation method to load nickel cations on the MFI molecular sieve crystals. Finally, it is dried, calcined in an air atmosphere, and reduced in a hydrogen atmosphere to obtain a nano nickel-based molecular sieve composite material with a core-shell structure.

[0038] The core-shell structured nano nickel-based molecular sieve composite material provided by the present invention can uniformly coat the crystallites loaded with nickel nanoparticles on the outer surface of the USY molecular sieve, and the shell thickness is relatively thin and adjustable (20 to 80 nm), which is beneficial to the diffusion of large molecular sulfides and hydrodesulfurization products, significantly improves the dispersibility of crystallites and nickel nanoparticles, improves the reaction activity, can reduce the mass transfer resistance of the hydrodesulfurization reaction, and is more conducive to the diffusion of large molecular organic sulfides such as 4,6-dimethyldibenzothiophene into the acidic sites in the crystallite pores. After reactions such as adsorption and alkyl transfer, the reaction of sulfur atoms with nickel nanoparticles is promoted to produce hydrogen sulfide and corresponding hydrocarbon products, showing excellent hydrodesulfurization performance.

[0039] The core-shell structured nano nickel-based molecular sieve composite material provided by the present invention has an Al-MFI content of 22.8wt% and a nickel content of 2.35wt%. When used as a catalyst in the hydrodesulfurization reaction of 4,6-dimethyldibenzothiophene, the conversion rate of 4,6-dimethyldibenzothiophene reaches 99.2%, and the desulfurization rate can reach 99.1%.

[0040] The preparation method provided by the invention has simple process, cheap and readily available raw materials, low production cost and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 X-ray diffraction patterns of samples USY@Al-MFI / NiO and USY@Al-MFI / Ni prepared in Example 4;

[0042] Figure 2 This is a high-magnification transmission electron microscopy image of the sample USY@Al-MFI / Ni prepared in Example 4 at 200nm;

[0043] Figure 3 This is a high-magnification transmission electron microscopy image of the sample USY@Al-MFI / Ni prepared in Example 4 at 500nm;

[0044] Figure 4 This is the electron diffraction pattern of the sample USY@Al-MFI / Ni prepared in Example 4;

[0045] Figure 5 It is a comparison chart of the conversion rate and desulfurization rate of the hydrodesulfurization experiments of Example 4, Comparative Application Example 1 and Comparative Application Example 2. DETAILED DESCRIPTION

[0046] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0047] The reagents used in the preparation process described below may be conventional reagents in the art or commercially available reagents; the methods adopted may be conventional means in the art or existing technologies.

[0048] The present invention provides a method for preparing a nano nickel-based molecular sieve composite material with a core-shell structure, comprising the following steps:

[0049] (1) adding a silicon source to an aqueous solution of tetrapropylammonium hydroxide, stirring and aging to fully hydrolyze the silicon source, then adding an aluminum source, continuing to stir and age to fully disperse the aluminum source in the solution; then performing a two-stage hydrothermal crystallization reaction to obtain an Al-MFI molecular sieve crystal solution containing acidic sites;

[0050] (2) adding USY zeolite molecular sieve to a cationic polyelectrolyte solution, mixing uniformly, centrifuging and washing the free polycations with distilled water, so that the polycations adhere to the outer surface of USY; then placing it in an anionic polyelectrolyte solution, centrifuging and washing the free polyanions with distilled water, so that the outer surface of USY is negatively charged; then placing it again in a cationic polyelectrolyte solution, centrifuging and washing the free polycations with deionization, so that the outer surface of USY is positively charged again, and repeatedly performing the above positive and negative charge coating process can increase the uniformity of the crystal particle coating;

[0051] (3) USY with positive charge on the outer surface is added to the Al-MFI crystallite solution and mixed evenly. Since the surface of the crystallite particles is negatively charged, under the action of positive and negative charges, the Al-MFI crystallite can be coated on the outer surface of the USY particles;

[0052] (4) centrifuging the USY coated crystals obtained in (3), washing them, and then placing them in a cationic polyelectrolyte solution, and repeating step (2) to make the outer surface of the composite structure positively charged again;

[0053] (5) placing the material obtained in step (4) into the crystallite solution again to achieve secondary coating of the crystallite particles. In order to adjust the thickness and uniformity of the shell layer, steps (4) and (5) may be repeatedly performed;

[0054] (6) The material obtained in (5) is added to an aqueous solution containing nickel ions to impregnate and load the nickel ions, and then washed, dried, calcined and reduced to obtain a nano nickel-based molecular sieve composite material with a core-shell structure.

[0055] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.

[0056] In the present invention, the silicon source preferably includes one or more of tetraethyl orthosilicate, water glass and silica sol; the aluminum source includes one or more of aluminum isopropoxide, aluminum nitrate nonahydrate, aluminum chloride hexahydrate and aluminum sulfate 18hydrate.

[0057] In the present invention, the molar ratio of silicon in the silicon source to tetrapropylammonium hydroxide is preferably 1:(0.15-0.6), more preferably 1:(0.2-0.5), and further preferably 1:0.4. The molar ratio of silicon in the silicon source to aluminum in the aluminum source is preferably 1:(0.025-0.005), more preferably 1:(0.017-0.008), and further preferably 1:(0.0137-0.01). The molar ratio of silicon in the silicon source to water is preferably 1:(4.5-40), more preferably 1:(10-30), and further preferably 1:(12-25).

[0058] In the present invention, the silicon source is added to the aqueous solution of tetrapropylammonium hydroxide, preferably tetrapropylammonium hydroxide is dissolved in water to obtain an aqueous solution of tetrapropylammonium hydroxide; then the silicon source is added to the aqueous solution of tetrapropylammonium hydroxide, and the present invention has no special limitation on the mixing method, and the raw materials can be mixed evenly, such as stirring and mixing. The present invention preferably also includes aging the mixed solution, the aging temperature is preferably room temperature, the aging time is preferably 3 to 36 hours, and more preferably 10 to 20 hours; during the aging process, tetraethyl orthosilicate is fully hydrolyzed and becomes transparent and clear.

[0059] The present invention adds the aluminum source to the mixed solution of the previous step, stirs and ages, and allows the aluminum source to be fully dispersed in the solution. The preferred aging temperature is room temperature, and the aging time is preferably 2 to 24 hours, more preferably 10 to 20 hours.

[0060] In the present invention, the two-stage hydrothermal crystallization reaction is a low-temperature hydrothermal crystallization reaction and a high-temperature hydrothermal crystallization reaction. The temperature of the low-temperature hydrothermal crystallization reaction is preferably 50 to 110°C, more preferably 70 to 100°C, and further preferably 85 to 95°C; the time of the low-temperature hydrothermal crystallization reaction is preferably 50 to 160 min, more preferably 80 to 130 min, and further preferably 90 to 110 min. In the present invention, the temperature of the high-temperature hydrothermal crystallization reaction is preferably 120 to 170°C, more preferably 145 to 165°C, and further preferably 150 to 160°C; the time of the high-temperature hydrothermal crystallization reaction is preferably 30 to 100 min, more preferably 30 to 80 min, and further preferably 30 to 60 min.

[0061] After the high-temperature hydrothermal crystallization reaction, the present invention preferably further comprises dialyzing the mixed solution after the high-temperature hydrothermal crystallization reaction to obtain a nano Al-MFI crystallite molecular sieve solution. In the present invention, the dialysis is preferably to place the reaction solution after the high-temperature hydrothermal crystallization reaction in a dialysis bag, and then place the dialysis bag in water for dialysis; the dialysis bag is preferably a cellulose semipermeable membrane with a molecular weight cutoff of 2 to 20KD; the dialysis temperature is preferably room temperature; the present invention has no special limitation on the time of the dialysis, and the dialysis can be performed until the liquid outside the dialysis bag is neutral, such as 24-48 hours; the role of the dialysis is to remove amorphous silicon and free tetrapropylammonium hydroxide.

[0062] The dialysis bag after the dialysis operation, in the present invention, is placed in a low-temperature oven to slowly concentrate the solution containing Al-MFI crystals to a certain concentration, the concentration temperature is preferably 30-80°C, more preferably 50-60°C; the concentration time is preferably 5-20h, more preferably 10-15h. The concentrated concentration of the Al-MFI crystal solution is preferably 1-5wt% by mass, more preferably 3-4wt%.

[0063] In the present invention, the size of the USY zeolite molecular sieve is preferably 100 to 1000 nm, more preferably 300 to 600 nm.

[0064] In the present invention, in step (2), the cationic polyelectrolyte comprises one of polydiallyldimethylammonium chloride, polyvinylpyridine, polyvinylamine, etc. or a mixture thereof; the cationic polyelectrolyte comprises one of polystyrene sodium sulfonate, sodium polyacrylate, etc. or a mixture thereof. The mass concentration of the aqueous solution of the cationic polyelectrolyte and the anionic polyelectrolyte is preferably 0.1 to 10 wt%, more preferably 0.5 to 10 wt%.

[0065] In the present invention, the USY zeolite molecular sieve is added to the polyelectrolyte solution, and the liquid-to-solid mass ratio is preferably 10 to 50, and more preferably 20 to 30. In the present invention, the USY zeolite molecular sieve is mixed uniformly in the polyelectrolyte solution, and the mixing method is not limited, and stirring is preferred; the mixing temperature is preferably room temperature; and the mixing time is preferably 0.5 to 5 hours, and more preferably 1 to 2 hours.

[0066] In the present invention, in the step (2), the positive and negative charge coating process is repeatedly performed, and the number of repetitions is preferably 1 to 5 times, and more preferably 2 to 3 times, which effectively improves the uniformity of the coating of the crystal particles.

[0067] In the present invention, in the step (3), USY with a positive outer surface is added to the Al-MFI crystallite solution, and the preferred liquid-to-solid mass ratio is 10 to 50, and more preferably 20 to 30. The USY with a positive outer surface is mixed evenly in the Al-MFI crystallite solution, and the mixing method is not limited, and stirring is preferred; the mixing temperature is preferably room temperature; and the mixing time is preferably 1 to 24 hours, and more preferably 10 to 15 hours.

[0068] In the present invention, in the step (4), step (2) is repeated to make the outer surface of the composite structure positively charged again, and the repetition conditions are the same as those of step (2);

[0069] In the present invention, in step (5), the secondary coating conditions of the crystalline particles are the same as those of the first coating; in order to adjust the thickness and uniformity of the shell layer, steps (4) and (5) are repeatedly performed, and the number of repetitions is preferably 1 to 5 times, and more preferably 2 to 3 times.

[0070] In the present invention, in step (6), the nickel ions in the nickel ion aqueous solution are derived from water-soluble nickel salts, including one or more of nickel nitrate, nickel chloride and nickel acetate. In the present invention, the preferred ratio of nickel to the total mass of USY and Al-MFI is 0.5-5wt%, more preferably 2-3.5wt%.

[0071] In the present invention, in the step (6), USY coated with Al-MFI crystals is added to an aqueous solution of nickel ions, stirred, and the water is slowly evaporated, preferably at a temperature of 40-80°C, more preferably 60-70°C.

[0072] In the present invention, in the step (6), the preferred calcination atmosphere is air, the preferred calcination temperature is 200-800°C, more preferably 300-700°C, and further preferably 500-600°C; the calcination time is preferably 2-8h, more preferably 3-7h, and further preferably 4-6h; the purpose of the calcination is to remove the template agent tetrapropylammonium hydroxide and polyelectrolyte molecules in the molecular sieve.

[0073] In the present invention, the reduction temperature is preferably 200-800°C, more preferably 300-700°C, and further preferably 350-600°C; the reduction time is preferably 2-8h, more preferably 3-7h, and further preferably 4-6h; in the present invention, the reduction is carried out under a hydrogen-protective atmosphere; the volume fraction of hydrogen in the hydrogen-protective atmosphere is preferably 5-15%, and more preferably 5-10%; the present invention has no special limitation on the protective atmosphere, and a protective atmosphere well known to those skilled in the art can be used, such as argon. In the present invention, during the reduction process, nickel ions are reduced to nickel element.

[0074] The invention uses common silicon source, tetrapropylammonium hydroxide, aluminum source and water-soluble nickel salt as raw materials to prepare nano nickel-based Al-MFI molecular sieve crystals. The raw materials are widely available, inexpensive and have low production costs.

[0075] The present invention also provides the use of the core-shell structured nano nickel-based molecular sieve composite material described in the above technical solution as a catalyst in hydrodesulfurization.

[0076] In the present invention, the hydrodesulfurization includes a deep hydrodesulfurization process of fuel oils such as gasoline and diesel. In the present invention, the sulfides in the fuel oils such as gasoline and diesel preferably include thiophene compounds, more preferably include one or more of benzothiophene, dibenzothiophene, substituted dibenzothiophene and naphthiophene, and more preferably include 4,6-dimethyldibenzothiophene.

[0077] In the present invention, the application method of the core-shell structured nano nickel-based molecular sieve composite material preferably comprises the following steps: mixing sulfide, organic solvent and the core-shell structured nano nickel-based molecular sieve composite material, and performing a hydrodesulfurization reaction under a hydrogen atmosphere.

[0078] In the present invention, the sulfur content in the sulfide is preferably 10 to 1500 ppm, more preferably 100 to 1000 ppm. In the present invention, the mass ratio of the sulfide to the core-shell structured nano nickel-based molecular sieve composite material is preferably (0.1 to 1):1, more preferably (0.3 to 0.5):1. In the present invention, the organic solvent preferably includes one or more of decahydronaphthalene, xylene, tetrahydronaphthalene and hexadecane; the mass ratio of the core-shell structured nano nickel-based molecular sieve composite material to the volume of the organic solvent is preferably 1 g: (100 to 200) mL, more preferably 1 g: (100 to 150) mL.

[0079] The present invention has no special limitation on the mixing method, as long as the raw materials can be mixed evenly, such as stirring and mixing; the present invention has no special limitation on the speed and time of the stirring and mixing, as long as the raw materials can be mixed evenly; in an embodiment of the present invention, the stirring speed is preferably 200-300r / min.

[0080] In the present invention, the initial pressure of the hydrogen is preferably 1-8MPa, more preferably 2-7MPa. In the present invention, the temperature of the hydrodesulfurization reaction is preferably 150-350°C, more preferably 177-327°C; the heating rate from room temperature to the temperature of the hydrodesulfurization reaction is preferably 10-30°C / min, more preferably 20°C / min; starting from the temperature rising to the temperature of the hydrodesulfurization reaction, the time of the hydrodesulfurization reaction is preferably 1-12h, more preferably 3-10h; the hydrodesulfurization reaction is preferably carried out under stirring conditions, and the present invention has no special restrictions on the stirring speed, as long as the hydrodesulfurization reaction can proceed smoothly; in an embodiment of the present invention, the stirring speed is preferably 200-300r / min; the hydrodesulfurization reaction is preferably carried out in a reactor, and the reactor is preferably sealed before use and high-purity hydrogen is introduced to replace the air in the reactor; the reactor is preferably a Parr high-pressure reactor.

[0081] After the hydrodesulfurization reaction, the present invention preferably further comprises post-treatment, and the post-treatment comprises: cooling the reaction liquid of the hydrodesulfurization reaction to room temperature. The present invention has no particular limitation on the cooling method, and any cooling method known in the art can be used, such as natural cooling.

[0082] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0083] Example 1

[0084] (1) Take 15.8621g of tetrapropylammonium hydroxide aqueous solution (TPAOH, mass fraction is 25%), drop it into 5.6624g of water, and stir to mix; then drop 10.5217g of tetraethyl orthosilicate (TEOS), stir at room temperature for 12h, so that tetraethyl orthosilicate is fully hydrolyzed; then take 0.1427g of aluminum isopropoxide and add it to the mixed solution, stir at room temperature for 6h, so that aluminum isopropoxide is fully dispersed in the mixed solution, and the molar ratio of raw materials SiO2:TPAOH:Al2O3:H2O in the mixed solution is 1:0.39:0.006 8:19.51; then put the above-mentioned mixed solution into the reactor, put it into the hydrothermal crystallization reactor, and crystallize it at 90°C for 90 minutes and at 160°C for 40 minutes; then immediately take out the reactor and cool it to room temperature with water; then put the reaction mixed solution into a dialysis bag, put it into a cellulose semipermeable membrane, soak it in water, and dialyze it at room temperature for 24 hours to obtain an Al-MFI molecular sieve crystallite solution; finally, put the dialyzed Al-MFI molecular sieve crystallite solution into a 50°C blast oven, slowly evaporate it, and concentrate it to a crystallite mass fraction of 3%.

[0085] (2) Take 1g of USY molecular sieve, add it to 30g of polydiallyldimethylammonium chloride (PDDA) aqueous solution (mass fraction is 3%), and stir at room temperature for 2h; then centrifuge and wash it with distilled water for 3 times to remove the unadsorbed PDDA molecules; then add the washed USY molecular sieve to 30g of polystyrene sulfonate sodium (PSS) aqueous solution (mass fraction is 3%), stir at room temperature for 2h; then centrifuge and wash it with distilled water for 3 times to remove the unadsorbed PSS molecules; then add the washed USY molecular sieve to 30g of PDDA aqueous solution (mass fraction is 3%), stir at room temperature for 2h; then centrifuge and wash it with distilled water for 3 times to remove the unadsorbed PDDA molecules; then centrifuge and wash it with distilled water for 3 times to remove the unadsorbed PSS molecules; The USY molecular sieve was placed into 20g of the concentrated Al-MFI molecular sieve crystal mixture in step (1) (the mass fraction of the crystallites is 3%), stirred at room temperature for 12h, centrifuged and the supernatant was retained (the content was measured and used as the raw material liquid for the second crystal coating), and the USY molecular sieve was washed twice with distilled water; then the USY crystallized once was coated with PDDA according to the same steps, and the USY surface was positively charged; finally, it was placed in the Al-MFI molecular sieve crystal solution after the above coating (the mass fraction has been measured to be 1.88%), stirred at room temperature for 12h, centrifuged and the supernatant was retained (the content was measured to be 0.66%), and the USY molecular sieve was washed twice with distilled water to remove a small amount of unabsorbed crystals.

[0086] (3) The USY molecular sieve coated with Al-MFI molecular sieve crystals twice was added to an aqueous solution of nickel nitrate (including 25g water and 0.2354g nickel nitrate hexahydrate), stirred at room temperature for 1h, and then stirred at 70°C to evaporate the water and load the nickel ions on the shell Al-MFI crystals; then placed in a muffle furnace and calcined at 550°C for 6h to remove impurities such as tetrapropylammonium hydroxide, polydiallyldimethylammonium chloride, sodium polystyrene sulfonate and nitrate; finally, reduced at 450°C in H2-Ar atmosphere (H2 volume fraction of 5%) for 4h, cooled to room temperature, and obtained a core-shell structured nano nickel-based molecular sieve composite material, in which the Ni loading was 3.18wt% (based on the sum of the mass of USY and Al-MFI molecular sieve crystals), and the sample was recorded as: USY@Al-MFI / Ni-3.18%.

[0087] Example 2

[0088] A core-shell structured nano nickel-based molecular sieve composite material was prepared according to the method of Example 1, which differs from Example 1 in that:

[0089] In step (1), aluminum isopropoxide is replaced with aluminum nitrate nonahydrate; and the mass fraction of the concentrated crystallization solution is adjusted to 3.5%.

[0090] In step (2), the concentration of the polydiallyldimethylammonium chloride aqueous solution is adjusted from 3% to 0.5%; sodium polystyrene sulfonate is replaced by sodium polyacrylate, and its concentration is adjusted from 3% to 1%. After the USY molecular sieve is coated with a cationic electrolyte once, it is centrifuged, washed with distilled water, and directly coated with the crystals.

[0091] In step (3), the calcination temperature is adjusted from 550°C to 500°C, the calcination time is adjusted from 6h to 8h, and the nickel loading is adjusted from 3.18% to 2.5%; the obtained core-shell structured nano nickel-based molecular sieve composite material is recorded as: USY@Al-MFI / Ni-2.5%.

[0092] Example 3

[0093] A core-shell structured nano nickel-based molecular sieve composite material was prepared according to the method of Example 1, which differs from Example 1 in that:

[0094] In step (1), aluminum isopropoxide is replaced with aluminum chloride hexahydrate, and TEOS is replaced with silica sol; the mass fraction of the concentrated crystallization solution is adjusted to 3.5%.

[0095] In step (2), the concentration of the PDDA aqueous solution is adjusted from 3% to 10%; the concentration of PSS is adjusted from 3% to 10%. The USY molecular sieve is coated with PDDA once, PSS once, then PDDA and PSS once, and then PDDA once, centrifuged, washed with distilled water, and directly coated with the first crystal.

[0096] In step (3), the calcination temperature is adjusted from 550°C to 600°C, the calcination time is adjusted from 6h to 4h, and the nickel loading is adjusted from 3.35% to 2.06%; the obtained core-shell structured nano nickel-based molecular sieve composite material is recorded as: USY@Al-MFI / Ni-2.06%.

[0097] Example 4

[0098] A core-shell structured nano nickel-based molecular sieve composite material was prepared according to the method of Example 1, which differs from Example 1 in that:

[0099] In step (1), aluminum isopropoxide is replaced with aluminum sulfate 18-hydrate, and the molar ratio of silicon to water is adjusted from 19.51 to 25; and the atomic ratio of silicon to aluminum is adjusted from 73 to 150.

[0100] In step (2), the concentration of the PDDA aqueous solution is adjusted from 3% to 10%; and the concentration of PSS is adjusted from 3% to 10%.

[0101] In step (3), the water volatilization temperature of the nickel ions loaded on the core-shell structure is adjusted from 70°C to 50°C; the nickel loading amount is adjusted from 3.35% to 2.35%; the H2-Ar atmosphere reduction temperature is adjusted from 450°C to 400°C, and the reduction time is adjusted from 4h to 6h. The obtained core-shell structured nano nickel-based molecular sieve composite material is recorded as: USY@Al-MFI / Ni-2.35%.

[0102] Example 5

[0103] A core-shell structured nano nickel-based molecular sieve composite material was prepared according to the method of Example 1, which differs from Example 1 in that:

[0104] In step (1), aluminum isopropoxide is replaced with aluminum nitrate nonahydrate, and the molar ratio of silicon to water is adjusted from 19.51 to 12; and the atomic ratio of silicon to aluminum is adjusted from 73 to 200.

[0105] In step (2), the concentration of the PDDA aqueous solution is adjusted from 3% to 1%; and the concentration of PSS is adjusted from 3% to 1%.

[0106] In step (3), the water volatilization temperature of the nickel ions loaded on the core-shell structure is adjusted from 70°C to 60°C; the nickel loading amount is adjusted from 3.35% to 2.75%; the H2-Ar atmosphere reduction temperature is adjusted from 450°C to 600°C, and the reduction time is adjusted from 4h to 3h. The obtained core-shell structured nano nickel-based molecular sieve composite material is recorded as: USY@Al-MFI / Ni-2.75%.

[0107] Comparative Example 1

[0108] Take 1g of core phase USY molecular sieve, immerse it in an aqueous solution of nickel nitrate hexahydrate, and slowly evaporate the water at 60°C (based on USY, the nickel loading is 2.35wt%); then put it in a muffle furnace and roast it at 550°C for 6h to remove impurities such as nitrate; finally, reduce it at 450°C in H2-Ar atmosphere (H2 volume fraction is 5%) for 4h, cool it to room temperature, and obtain a USY catalyst loaded with nickel nanoparticles. The sample is recorded as: USY / Ni-2.35%

[0109] Comparative Example 2

[0110] Take 1g USY molecular sieve, add it to 30g polydiallyldimethylammonium chloride (PDDA) aqueous solution (mass fraction is 3%), stir at room temperature for 2h; then centrifuge and wash it with distilled water for 3 times; then add the washed USY molecular sieve to 30g polystyrene sulfonate (PSS) aqueous solution (mass fraction is 3%), stir at room temperature for 2h; then centrifuge and wash it with distilled water for 3 times; then add the washed USY molecular sieve to 30g PDDA aqueous solution (mass fraction is 3%), stir at room temperature for 2h; then centrifuge and wash it with distilled water for 3 times; then put the washed USY molecular sieve into 20 g concentrated Al-MFI molecular sieve crystal mixture (crystal mass fraction is 3wt%), stirred at room temperature for 12h, centrifuged and retained the supernatant (measured content, and used as the raw material solution for the second crystal coating), washed the USY molecular sieve twice with distilled water; then the USY coated with crystals once was coated with PDDA according to the same steps, and the USY surface was positively charged; finally, it was placed in the Al-MFI molecular sieve crystal solution after coating once (the mass fraction has been measured to be 1.81%), stirred at room temperature for 12h, centrifuged and retained the supernatant (measured content is 0.52%), and washed the USY molecular sieve twice with distilled water.

[0111] The USY molecular sieve coated twice with Al-MFI molecular sieve crystals was placed in an oven at 80°C and dried for 12 hours to remove moisture; then it was placed in a muffle furnace and calcined at 550°C for 6 hours to remove impurities such as TPAOH, PDDA and PSS; and USY coated with Al-MFI molecular sieve crystals was obtained, and the sample was recorded as: USY@Al-MFI.

[0112] Figure 1 This is the X-ray diffraction pattern of the sample (USY@Al-MFI / NiO) in Example 4 after USY was coated twice with Al-MFI molecular sieve crystals, then impregnated with nickel ions, and then calcined in an air atmosphere in a muffle furnace. Compared with the pure USY molecular sieve, after calcination, the characteristic diffraction peaks of NiO were not found at 37.25° and 43.275°; at the same time, for the sample USY@Al-MFI / Ni-2.35% after hydrogen reduction, the characteristic diffraction peaks of Ni nanoparticles were not found at 44.5°, 51.8°, and 76.4°, which indicates that the distribution of nickel nanoparticles is relatively uniform and the particle size is small, and therefore no X-ray characteristic diffraction peaks are shown.

[0113] Figures 2 to 4 The high-power transmission electron microscope image of the USY@Al-MFI / Ni-2.35% material in Example 4 and the electron diffraction pattern of the core phase USY are shown in the figure. It can be seen from the figure that after high-temperature calcination in a muffle furnace and reduction treatment in a hydrogen atmosphere, the core-shell structure of USY@Al-MFI / Ni-2.35% is clearly present. Specifically, the thickness of the shell phase Al-MFI molecular sieve crystals is 30-40nm, and no obvious long-range lattice fringes are found. Figure 1 The characteristic diffraction peak of MFI is not shown in the electron diffraction pattern of the core phase region. It can be seen from the electron diffraction pattern of the core phase USY molecular sieve that the crystal structure is complete and the core phase size is about 500nm.

[0114] Application Example 1

[0115] The hydrodesulfurization experiment was carried out in a Parr high-pressure reactor (100 mL reactor volume). First, 10 mL of 4,6-dimethyldibenzothiophene decahydronaphthalene solution (4,6-dimethyldibenzothiophene, DMDBT, 500 ppm) was added to the reactor, and then 0.1 g of USY@Al-MFI / Ni-3.18% catalyst was added; then the reactor was sealed, and high-purity hydrogen was introduced to replace the air in the reactor, and repeated 3 times, and finally the initial hydrogen partial pressure in the reactor was maintained at 6 MPa; the stirring was turned on, the speed was 200 r / min, and the temperature was raised to 260°C at a rate of 20°C / min, and the heating was turned off. With the help of the "flying temperature" phenomenon, the temperature in the reactor was raised to 290°C, and the heating was turned on again and maintained at 300°C. The hydrodesulfurization reaction was carried out for 5 hours, and the heating was stopped, cooled to room temperature, centrifuged, and the supernatant was taken and passed through a 0.22 μm microfilter.

[0116] The DMDBT conversion rate was determined by comparing the retention time of gas chromatography and standards, and detected by a flame ionization detector (FID) on a Shimadzu GC2010 chromatograph, with a chromatographic column of HP-5 (0.25mm×30m×0.2μm). The chromatographic analysis conditions were: carrier gas N2 flow rate of 30mL / min, H2 flow rate of 40mL / min, air flow rate of 400mL / min, split ratio of 100:1; injection port temperature of 280℃, FID detector temperature of 300℃, injection volume of 1μL. The specific program heating program was: initial temperature 100℃, maintained for 10min, heated to 280℃ at a heating rate of 10℃ / min, and maintained for 5min. The DMDBT conversion rate calculation formula is as follows:

[0117] Conversion(%)=(1-Cp / Cr)×100%

[0118] where Cp and Cr represent the concentrations of DMDBT in the reaction and product, respectively.

[0119] The filtered liquid product was tested on a GCTNS-3000 sulfur and nitrogen analyzer (Jiangsu Guochuang Analytical Instrument Co., Ltd.). The desulfurization rate was calculated using the following formula:

[0120] Desulfidation degree(%)=(1-Sp / Sr)×100%

[0121] Where Sp and Sr represent the sulfur content in the reaction and product, respectively.

[0122] For the USY@Al-MFI / Ni-3.18% catalyst, the calculated conversion of 4,6-dimethyldibenzothiophene was 100% and the desulfurization rate was 99.6%.

[0123] Application Example 2

[0124] The hydrodesulfurization reaction of 4,6-dimethyldibenzothiophene was carried out according to the method of Application Example 1. The difference from Application Example 1 is that 0.102 g of USY@Al-MFI / Ni-2.5% catalyst was added, and the calculated 4,6-dimethyldibenzothiophene conversion rate was 100% and the desulfurization rate was 99.9%.

[0125] Application Example 3

[0126] The hydrodesulfurization reaction of 4,6-dimethyldibenzothiophene was carried out according to the method of Application Example 1. The difference from Application Example 1 is that 0.103 g of USY@Al-MFI / Ni-2.06% catalyst was added, and the calculated 4,6-dimethyldibenzothiophene conversion rate was 98.2%, and the desulfurization rate was 98.3%.

[0127] Application Example 4

[0128] The hydrodesulfurization reaction of 4,6-dimethyldibenzothiophene was carried out according to the method of Application Example 1. The difference from Application Example 1 is that 0.103 g of USY@Al-MFI / Ni-2.35% catalyst was added, and the calculated 4,6-dimethyldibenzothiophene conversion rate was 99.2%, and the desulfurization rate was 99.1%.

[0129] Application Example 5

[0130] The hydrodesulfurization reaction of 4,6-dimethyldibenzothiophene was carried out according to the method of Application Example 1. The difference from Application Example 1 is that 0.103 g of USY@Al-MFI / Ni-2.75% catalyst was added, and the calculated 4,6-dimethyldibenzothiophene conversion rate was 100% and the desulfurization rate was 99.2%.

[0131] Application Example 6

[0132] The hydrodesulfurization reaction of 4,6-dimethyldibenzothiophene was carried out according to the method of Application Example 1, except that 1000 ppm of 4,6-dimethyldibenzothiophene was added, the temperature of the hydrodesulfurization reaction was 350°C, the time was 8 hours, and the initial partial pressure of hydrogen was 6 MPa. The conversion rate of 4,6-dimethyldibenzothiophene was 100%, and the desulfurization rate was 99.9%.

[0133] Application Example 7

[0134] The hydrodesulfurization reaction of dibenzothiophene is carried out according to the method of Application Example 1, which is different from Application Example 1 in that:

[0135] Take 25mL of the sulfur-containing model oil prepared according to step 1.1 and 200mg of USY@Al-MFI / Ni-2.35% catalyst and add them to a 100mL high-temperature and high-pressure reactor (Shanghai Laibei Scientific Instruments, LB100-C276), seal the reactor, connect the circulating water, and check the thermocouple. Use nitrogen to replace the air in the reactor, and then replace it with hydrogen 5 times to ensure that the reactor is completely filled with H2. Fill H2 at room temperature to make the initial pressure in the reactor reach 3.6MPa. Temperature reaction: Turn on the mechanical stirring of the reactor, the speed is about 500rpm, turn on the circulating water, and raise it to 260℃ at a rate of 5℃ / min, and keep it for 10min; then continue to raise it to 320℃ at a rate of 5℃ / min (about 68min in total), the reaction pressure reaches about 6MPa, and the reaction is 9h.

[0136] Sampling analysis: After the reaction is completed, the stirring, circulating water and heating switches are turned off, and the kettle body temperature is reduced to room temperature, and then the pressure is released and the kettle is disassembled. The reaction product is taken out and centrifuged, and the supernatant is analyzed according to the above application example 1. The conversion rate of dibenzothiophene is calculated to be 98.2%, and the desulfurization rate is 97.5%.

[0137] Comparative application example 1

[0138] The hydrodesulfurization reaction of 4,6-dimethyldibenzothiophene was carried out according to the method of Application Example 1. The difference from Application Example 1 is that 0.103 g of USY / Ni-2.35% catalyst was added, and the calculated 4,6-dimethyldibenzothiophene conversion rate was 86.2% and the desulfurization rate was 65.1%.

[0139] Comparative Application Example 2

[0140] The hydrodesulfurization reaction of 4,6-dimethyldibenzothiophene was carried out according to the method of Application Example 1. The difference from Application Example 1 is that 0.104 g of USY@Al-MFI catalyst was added, and the calculated 4,6-dimethyldibenzothiophene conversion rate was 88.6%, and the desulfurization rate was 48.5%.

[0141] Figure 5 The results of the hydrodesulfurization reactions of Application Example 4 and Comparative Application Examples 1 and 2 show that the core-shell structured nano nickel-based molecular sieve composite material has excellent 4,6-dimethyldibenzothiophene conversion rate and desulfurization rate.

[0142] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a nano nickel-based molecular sieve composite material with a core-shell structure, characterized in that: The composite material is a core-shell structure, the core phase is USY zeolite, and the shell phase is Al-MFI molecular sieve crystals loaded with nickel nanoparticles. In terms of weight percentage, USY zeolite is 50-80%, and Al-MFI molecular sieve crystals loaded with nickel nanoparticles are 20-50%. The preparation method comprises the following steps: S1: dissolving the silicon source and the aluminum source in an aqueous solution of tetrapropylammonium hydroxide in sequence, and obtaining an Al-MFI molecular sieve crystal solution containing acidic sites after hydrothermal treatment; S2: adding USY zeolite to a cationic polyelectrolyte solution and mixing it evenly, so that polycations are attached to the surface of the USY zeolite, and the free polycations are removed by centrifugal washing; then placing it in an anionic polyelectrolyte solution and mixing it evenly, so that polyanions are attached to the surface of the USY zeolite, and the free polyanions are removed by centrifugal washing; placing it in a cationic polyelectrolyte solution again and mixing it evenly, so that polycations are attached to the surface of the USY zeolite, and the free polycations are removed by centrifugal washing; repeating the above steps several times to increase the uniformity of the coating of the crystal particles, and obtaining a positively charged USY zeolite with attached polyelectrolyte; S3: adding the positively charged USY zeolite with attached polyelectrolyte obtained in step S2 to the Al-MFI molecular sieve crystallite solution containing acidic sites obtained in step S1 and mixing them evenly, and under the action of charge matching, the Al-MFI molecular sieve crystallite is coated on the outer surface of the USY zeolite particles to obtain USY zeolite coated with the Al-MFI molecular sieve crystallite; S4: centrifuging and washing the USY zeolite coated with Al-MFI molecular sieve crystals obtained in step S3, then placing it in a cationic polyelectrolyte solution and mixing it evenly, repeating step S2 to obtain the USY zeolite coated with Al-MFI molecular sieve crystals with a positive outer surface; S5: adding the USY zeolite coated with Al-MFI molecular sieve crystals having positive outer surface obtained in step S4 to the Al-MFI molecular sieve crystal solution containing acidic sites obtained in step S1 again, performing secondary coating to adjust the thickness and uniformity of the shell layer, and repeating step S4 and the above steps several times to obtain a composite material; S6: adding the composite material obtained in step S5 into an aqueous solution containing nickel ions to impregnate and load the nickel ions, and after washing, drying, calcining and reducing, obtaining the nano nickel-based molecular sieve composite material with a core-shell structure.

2. The method for preparing a nano nickel-based molecular sieve composite material with a core-shell structure according to claim 1, characterized in that: The thickness of the shell layer is 20-80 nm, the loading amount of nickel nanoparticles is 0.5-5wt% of the total mass of USY zeolite and Al-MFI molecular sieve crystals, and the silicon-aluminum atomic ratio of the Al-MFI molecular sieve crystals is 35-200:

1.

3. The method for preparing a nano nickel-based molecular sieve composite material with a core-shell structure according to claim 1, characterized in that: In step S1, The silicon source comprises one or more of tetraethyl orthosilicate, water glass and silica sol, the aluminum source comprises one or more of aluminum isopropoxide, aluminum nitrate nonahydrate, aluminum chloride hexahydrate and aluminum sulfate 18hydrate, and the molar ratio of silicon element in the silicon source, aluminum element in the aluminum source, tetrapropylammonium hydroxide and water is 1:0.025~0.005:0.15~0.6:4.5~40; The hydrothermal treatment includes two stages of hydrothermal crystallization reactions, which are low-temperature hydrothermal crystallization reaction and high-temperature hydrothermal crystallization reaction. The temperature of the low-temperature hydrothermal crystallization reaction is 50-110°C and the time is 50-160 min. The temperature of the high-temperature hydrothermal crystallization reaction is 120-170°C and the time is 30-100 min. The size of the crystallite particles in the Al-MFI molecular sieve crystallite solution containing acidic sites is 6-20 nm.

4. The method for preparing a nano nickel-based molecular sieve composite material with a core-shell structure according to claim 1, characterized in that: In step S2, The size of the USY zeolite is 100-1000 nm, the cationic polyelectrolyte includes one or more of polydiallyldimethylammonium chloride, polyvinylpyridine and polyvinylamine, and the anionic polyelectrolyte includes one or more of sodium polystyrene sulfonate and sodium polyacrylate; the cationic polyelectrolyte solution is an aqueous solution of a cationic polyelectrolyte with a mass concentration of 0.1-10 wt%, and the anionic polyelectrolyte solution is an aqueous solution of an anionic polyelectrolyte with a mass concentration of 0.1-10 wt%; The mixing time is 0.5~5h, and the steps are repeated 1~5 times.

5. The method for preparing a nano nickel-based molecular sieve composite material with a core-shell structure according to claim 1, characterized in that: In step S3, The positively charged USY zeolite with attached polyelectrolyte is added into the Al-MFI molecular sieve crystal solution containing acidic sites, the liquid-to-solid mass ratio is 10-50, and the mixing time is 1-24 hours.

6. The method for preparing a nano nickel-based molecular sieve composite material with a core-shell structure according to claim 1, characterized in that: In step S4, The cationic polyelectrolyte includes one or more of polydiallyldimethylammonium chloride, polyvinylpyridine and polyvinylamine, and the anionic polyelectrolyte includes one or more of sodium polystyrene sulfonate and sodium polyacrylate; the cationic polyelectrolyte solution is an aqueous solution of a cationic polyelectrolyte with a mass concentration of 0.1-10 wt%, and the anionic polyelectrolyte solution is an aqueous solution of an anionic polyelectrolyte with a mass concentration of 0.1-10 wt%. The mixing time is 0.5~5h, and the steps are repeated 1~5 times.

7. The method for preparing a nano nickel-based molecular sieve composite material with a core-shell structure according to claim 1, characterized in that: In step S5, The USY zeolite coated with Al-MFI molecular sieve crystals having a positive outer surface is added again into the Al-MFI molecular sieve crystal solution containing acidic sites, the liquid-to-solid mass ratio is 10-50, and the steps are repeated 1-5 times.

8. The method for preparing a nano nickel-based molecular sieve composite material with a core-shell structure according to claim 1, characterized in that: In step S6, The nickel ions in the aqueous solution containing nickel ions are derived from water-soluble nickel salts, including one or more of nickel nitrate, nickel chloride and nickel acetate; The calcination atmosphere is air, the temperature is 200-800°C, and the time is 2-8h; The reducing atmosphere is a hydrogen-protective gas atmosphere, the temperature is 200-800° C., and the time is 2-8 hours, wherein the hydrogen volume fraction in the hydrogen-protective gas atmosphere is 5-15%.

9. Use of a nano nickel-based molecular sieve composite material with a core-shell structure prepared by the preparation method according to any one of claims 1 to 8 as a catalyst in hydrodesulfurization.

Citation Information

Patent Citations

  • Core-shell USY@SBA-15 composite material as well as preparation method and application thereof

    CN103191771A

  • Nano nickel-based MFI crystallite molecular sieve as well as preparation method and application thereof

    CN114308116A